2010
DOI: 10.1021/ja103275u
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Control of Structural Order in N-Alkylthieno[3,4-c]pyrrole-4,6-dione-Based Polymers for Efficient Solar Cells

Abstract: The correlation between the nature of alkyl substituents on N-alkylthieno[3,4-c]pyrrole-4,6-dione (TPD)-based polymers and solar cell device performance has been investigated. After adjusting device parameters, these TPD-based polymers used with PC(61)BM provided photovoltaic responses ranging from 4.0% to 6.8%, depending on the size and shape of the alkyl solubilizing groups. Further, we have correlated the effect of the alkyl groups on the structural order and orientation of the polymer backbone using grazin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
760
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 899 publications
(788 citation statements)
references
References 32 publications
26
760
0
2
Order By: Relevance
“…This has been shown to improve current in devices by strengthening polymer/PCBM interactions and as such the synthesis and device performance of high molecular weight N -1-ethylpentyl alkylated TPD-2T will be of interest. [14,16] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been shown to improve current in devices by strengthening polymer/PCBM interactions and as such the synthesis and device performance of high molecular weight N -1-ethylpentyl alkylated TPD-2T will be of interest. [14,16] …”
Section: Resultsmentioning
confidence: 99%
“…Email: jwrumer@imperial.ac.uk comparison of branched and linear alkyl chains, evaluating their effect on device performance, with the former preferred for organic photovoltaic applications and the latter for transistors. [16,17] More recently, a number of studies have begun to elucidate the effect of precision alkyl-chain engineering by shifting the branching point position, which has resulted in both improved photovoltaic efficiency and charge carrier mobility in field-effect transistors. [18][19][20] However, the preferred side-chain is largely dependent on the exact polymer system.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,4,21,53 Similarly, several low band-gap polymers were reported using the electron-deficient TPD unit. 13,15,17,18,54 For example, Frechet et al reported polymers (P1-3) bearing BDT and TPD units with variable alkyl side chains attached to the TPD unit. 15 Among these, P3 containing a less bulky octyl side chain on the TPD unit, exhibited enhanced p-p ordering and crystallinity in the solid state, even in the presence of PCBM.…”
Section: Synthetic Strategy: Ingredients For High-perform-ance Polymersmentioning
confidence: 99%
“…13,15,17,18,54 For example, Frechet et al reported polymers (P1-3) bearing BDT and TPD units with variable alkyl side chains attached to the TPD unit. 15 Among these, P3 containing a less bulky octyl side chain on the TPD unit, exhibited enhanced p-p ordering and crystallinity in the solid state, even in the presence of PCBM. 15 Interestingly, the PDTSTPD polymer containing TPD and silicon-bridged DTS units exhibited increased solid-state ordering and a lower HOMO energy level compared to the corresponding carbonbased fused rings.…”
Section: Synthetic Strategy: Ingredients For High-perform-ance Polymersmentioning
confidence: 99%
See 1 more Smart Citation